Developing a business plan for an online crowd gifting platform - Nesan, Ashvin (2018)
The wedding and events industry is a multi-billion dollar industry that only seems to keep growing. Even in Malaysia, this events and functions are celebrated more lavishly and extravagantly than ever before. Over time, a number of services that are related to this events such as designing of invitation cards, booking of event space and or even buying accessories and clothes for the wedding entourage, have been done over the internet instead of in conventional brick and mortar stores. The act of gifting in the industry though, has stood the test of time thus far and remained largely unchanged from as far back as one can remember.